Ruptures in the Western Empire : White Female Captives and Cinematic Orientalism. - Moumni, Omar (Cambridge Scholars Pub., 2012)
First encounters between the east and the west in the Mediterranean are important instances in history. They are the source of constructing a myth and history that has depended much on literary and cultural productions. This book investigates this history by dwelling on issues of white female captives in Moorish Thralldom and their representation in western cinema to realize the way the stories of those Christian female captives have been used and abused by their nations to achieve imperialis ...